METODE PEMBINAAN AKHLAK ANAK USIA SEKOLAH DASAR OLEH ORANGTUA PADA MASA NEW NORMAL DI JORONG GADUANG KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Delfita Mutiara; Iswantir Iswantir; Afrinaldi Afrinaldi; Arifmiboy Arifmiboy (KOLONI, 2022)
The background of this research is that at this time in Jorong Gaduang when children are in the education process at home or in the new normal period of education, children should get full attention in terms of moral development. However, moral development at home indicates that there are methods or methods from some parents in Jorong Gaduang in fostering the morals of children who are lacking. The less than optimal method of moral development given by the parents such as parents do not provide a good example at home. In addition, parents also do not pay attention to or supervise the use of gadgets and the association of children’s peers. Then there are also parents who do not give advice and punishment to children when they make mistakes. The lack of application of several methods of moral development carried out by parents is because parents are busy with their respective jobs. This type of research is research that is a type of research that is field research, with a qualitative descriptive approach. From the research that has been done, it can be concluded that parents have fostered the morals of elementary school-aged children with various methods, namely the exemplary method, the habituation method, the advice method, the punishment method and the attention method. In addition to applying these 5 methods during the new normal, parents also apply the method of giving gifts and the story method in fostering children’s morals. Those who behave badly are caused because there are several obstacles for parents in fostering morals during the new normal period, namely: a) parental responsibility for children while studying at home is lacking, namely time constraints. B) Parents have difficulty controlling the use of online media, namely the use of gadgets. C) The difficulty of parents in controlling their children’s association with peers, causing children to play more than study, worship and help their parents. Keywords: Child coaching method, elementary school age children, new normal